2016
DOI: 10.1103/physrevlett.116.183901
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of Geometric Parametric Instability Induced by the Periodic Spatial Self-Imaging of Multimode Waves

Abstract: Spatiotemporal mode coupling in highly multimode physical systems permits new routes for exploring complex instabilities and forming coherent wave structures. We present here the first experimental demonstration of multiple geometric parametric instability sidebands, generated in the frequency domain through resonant space-time coupling, owing to the natural periodic spatial self-imaging of a multimode quasi-continuous-wave beam in a standard graded-index multimode fiber. The input beam was launched in the fib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
195
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(206 citation statements)
references
References 41 publications
11
195
0
Order By: Relevance
“…
Multimode optical fibres are enjoying a renewed attention, boosted by the urgent need to overcome the current capacity crunch of single-mode fibre systems and by recent advances in multimode complex nonlinear optics [1][2][3][4][5][6][7][8][9][10][11][12][13]. In this work, we demonstrate that standard multimode fibres can be used as ultrafast all-optical tool for transverse beam manipulation of high power laser pulses.
…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…
Multimode optical fibres are enjoying a renewed attention, boosted by the urgent need to overcome the current capacity crunch of single-mode fibre systems and by recent advances in multimode complex nonlinear optics [1][2][3][4][5][6][7][8][9][10][11][12][13]. In this work, we demonstrate that standard multimode fibres can be used as ultrafast all-optical tool for transverse beam manipulation of high power laser pulses.
…”
mentioning
confidence: 94%
“…In fibres with parabolic index profile, the propagation constants of the modes take equally spaced values, so that coherent mode beating induces a periodic local intensity oscillation along the fibre, which the Kerr effect translates into a periodic longitudinal modulation of the refractive index [4,10,12]. With a simpler two-mode excitation, such type of self-induced or dynamic long-period Bragg grating was previously exploited in [25] for demonstrating light-controlled mode conversion in a GRIN MMF.…”
mentioning
confidence: 99%
“…As the number of guided modes increases, one must eventually expect the numerical complexity of the method to scale as OMN P. One can improve this to ON P by abandoning the modal expansion entirely [9], evaluating the linear dispersion operator in real space by finite-differences, or possibly 2D FFTs (in which case one has OPN log N scaling). In this case, however, the dispersion operator is approximated, and P must be chosen large enough to obtain a satisfactory accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between different guided modes can lead to phase-matched four-wave mixing over wide frequency ranges and with pump wavelengths in the normal-dispersion regime of the fibers [4][5][6]. Pumping large-core multimode fibers with a parabolic index variation to minimize walkoff between guided modes has been shown to enable complex intermodal nonlinear interactions, in particular enabling short-wavelength dispersive-wave generation from soliton collapse and spatiotemporal soliton oscillations at elevated pulse energies [7,8], and sideband formation from geometric parametric instabilities [9]. Also, in the emerging low-loss hollow-core fibers guiding by antiresonant effects, intermodal nonlinearities can be important for the highly interesting frequency-conversion processes enabled by these waveguides [10].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate a new way to simultaneously control the frequency and modal content of multimode beams. Namely, we experimentally observed that the natural periodic self-imaging of multimode waves leads, via spatiotemporal modulation instability, to the generation of a series of spatially coherent sidebands with exceptionally large frequency shifts [6].…”
Section: Introductionmentioning
confidence: 99%